Pengembangan Media Pembelajaran Matematika Berbantu Adobe Flash Melalui Etnomatematika Pada Rumah Adat Lampung - Resty Khairina Vevi Martyas Pratami; Dona Dinda Pratiwi; Mohammad Muhassin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
This research was conducted to determine the appropriateness of learning media and to know the response of the learners to the mathematics learning media assisted by Adobe Flash through ethnomathematics on Lampung Traditional House for eight grade of junior high school on polyhedron subject. This research type was research and development (R&D). The research and development steps were based on the Bord and Gall model. The instrument of data collecting was questionnaire with Likert scale. The data analysis technique used in this research was quantitative descriptive data analysis. The result of the research of mathematics learning media assisted by Adobe Flash through Ethnomathematics at Lampung Traditional House obtained the average value of material experts 3.62, media experts 3.47, linguists 3.67, and cultural experts 3.50 with